THE TYPIFICATION OF GIGANTOCHLOA TALUH WIDJAJA & ASTUTI (POACEAE, BAMBUSOIDEAE) - I Putu Gede P. Damayanto; Himmah Rustiami; Miftahudin Miftahudin; Tatik Chikmawati (Research Center for Biology, 2023)
The name of Gigantochloa taluh Widjaja & Astuti (Poaceae, Bambusoideae) was invalid because of failure to meet the requirements of the International Code of Nomenclature for algae, fungi, and plants, that there was no herbarium location of type specimens was mentioned. A typification was provided here to address this issue.